2020
DOI: 10.22487/ghidza.v4i1.44
|View full text |Cite
|
Sign up to set email alerts
|

Komposisi Menu Sarapan dan Status Gizi Pelajar Boarding School SMP Muhammadiyah 5 Samarinda

Abstract: Remaja awal memiliki kecenderungan untuk mengkonsumsi sarapan dalam komposisi yang tidak lengkap berdasarkan konsep gizi seimbang. Komposisi yang tidak lengkap dapat menyebabkan tidak terpenuhinya asupan gizi harian remaja yang berimpilkasi terhadap gangguan gizi maupun kesehatan. Tujuan penelitian ini adalah untuk mengetahui gambaran perilaku sarapan siswa-siswi salah satu SMP swasta unggulan di Kota Samarinda yang terdiri dari komposisi menu sarapan serta waktu sarapan serta menilai hubungan antara komposisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A typical breakfast cannot determine a person's nutritional status because the total energy requirement obtained from breakfast food is only 25% [38]. So, a balance breakfast menu is needed to fulfill the daily nutritional intake [86]. Previous studies demonstrated that there is no association between breakfast habits and the nutritional in high school students [85,87].…”
Section: Resultsmentioning
confidence: 99%
“…A typical breakfast cannot determine a person's nutritional status because the total energy requirement obtained from breakfast food is only 25% [38]. So, a balance breakfast menu is needed to fulfill the daily nutritional intake [86]. Previous studies demonstrated that there is no association between breakfast habits and the nutritional in high school students [85,87].…”
Section: Resultsmentioning
confidence: 99%